Torsional response of pretensioned elastic rods. (15th May 2020) - Kocakaplan, Sedef; Tassoulas, John L.
Highlights: Elastic, pretensioned circular rods are examined. A two-node hyperelement is developed for efficient computation of torsional response. The effect of pretension on the static torsional stiffness is investigated. The effect of pretension on the dynamic torsional stiffness is explored. It is shown that both static and dynamic tests can be used to estimate the level of pretension and the coefficient quantifying the influence of pretension on material behavior. Abstract: We examine the torsional response of a pretensioned elastic circular rod. First, we review a procedure for computation of semidiscrete wave modes in the rod. The modes are continuous in the axial and circumferential directions but discrete in the radial direction. In terms of these modes, we synthesize a two-node hyperelement that can represent a rod segment, with discretization only in the radial direction, within the framework of finite element analysis. The effort involved in computations with this hyperelement is independent of the rod segment length. Next, using this efficient formulation, we analyze time-harmonic vibrations of a pretensioned rod subjected to torque at one end and fixed at the other. We show how the rod response is affected by the level of pretension. Assuming that torsional-response measurements are available for a known level of pretension, we show how the coefficient describing the effect of pretension can be estimated. Finally, with this coefficient, we present a simple, yet effective, procedure for estimation of the level of pretension.